Forensic psychology - Gredecki, Neil; Turner, Polly (Topics in applied psychology series, 2022)
"Drawing on psychological theory and research, this text outlines the core roles of the forensic psychology profession, providing students with a broad overview of the field and bringing to life the work of the forensic psychologists. Written by leading UK practitioners and researchers working in a range of contexts, it invites students to reflect on how psychological literature helps us to understand people in contact with the justice system. Forensic psychology is continually evolving as a discipline and profession, shaping, and responding to changes in legal processes, policies and provision. This book highlights the work of forensic psychologists, which covers a range of areas including assessment and intervention, applied research, consultancy and the training and development of staff working in forensic services such as secure services or community settings. Case studies are used to link psychological theory to practice, showcasing the latest developments in the field, providing students with insights into best practice. The book further challenges myths in the field, encouraging students to humanise human harm and to apply compassion in their understanding of offending behaviour. Each chapter includes tasks and scenarios to promote critical thinking around theory and practice in what is an exciting time to work in this evolving field. As a field of study, and a profession within the systems for criminal and civil justice, forensic psychology overlaps and interacts with many other areas within and outside of psychology. As such, this volume details the contribution of forensic psychology to a range of presentations and organizational and professional issues, and is an ideal resource for courses in Forensic Psychology"--